Dėl vieno kelio raiškos atvejo Mikalojaus Daukšos Postilėje - Žilinskaitė, Eglė (Baltistica, 2006)
EXPRESSING A PARTICULAR MEANING OF WAY IN MIKALOJUS DAUKŠA’S POSTILLA The article centers on the means of expressing the meaning of a way through an object (such as window, door, hole, gateway) in Daukša’s Postilla and some other works from the 16th-17th century (Jaknavičius’, Bretkūnas’, Morkūnas’Postilla and Knyga nobažnystės krikščioniškos). The latter meaning is expressed by using instrumental and prepositional phrases perAcc and proAcc. Daukša’s Postilla and other books translated from Polish reveal that the usage of instrumental is determined by Polish texts, but it is also impossible to discount a possibility of the influence of the Latin ablative as well.